Licochalcone A is a natural selective inhibitor of arginine methyltransferase 6. Issue 2 (29th January 2021) - Gong, Shuai; Maegawa, Shinji; Yang, Yanwen; Gopalakrishnan, Vidya; Zheng, Guangrong; Cheng, Donghang
Abstract : Arginine methylation is a post-translational modification that is implicated in multiple biological functions including transcriptional regulation. The expression of protein arginine methyltransferases (PRMT) has been shown to be up-regulated in various cancers. PRMTs have emerged as attractive targets for the development of new cancer therapies. Here, we describe the identification of a natural compound, licochalcone A, as a novel, reversible and selective inhibitor of PRMT6. Since expression of PRMT6 is up-regulated in human breast cancers and is associated with oncogenesis, we used the human breast cancer cell line system to study the effect of licochalcone A treatment on PRMT6 activity, cell viability, cell cycle, and apoptosis. We demonstrated that licochalcone A is a non-S-adenosyl L-methionine (SAM) binding site competitive inhibitor of PRMT6. In MCF-7 cells, it inhibited PRMT6-dependent methylation of histone H3 at arginine 2 (H3R2), which resulted in a significant repression of estrogen receptor activity. Licochalcone A exhibited cytotoxicity towards human MCF-7 breast cancer cells, but not MCF-10A human breast epithelial cells, by up-regulating p53 expression and blocking cell cycle progression at G2/M, followed by apoptosis. Thus, licochalcone A has potential for further development as a therapeutic agent against breast cancer.